Arabic Lexicology - Safei, Su'aidi (2001)
The Parent-Teacher Association (PTA) of Madrasah al-Junied al-Islamiyyah organized Arabic class on Arabic Lexicology (ilm al-Ma’ajim) for adult. It was to enhance the parents’ Arabic knowledge and to expose them to the practical use of dictionaries that they can later on apply individually in their reading.